2019
DOI: 10.1108/ijem-12-2017-0365
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support and organizational commitment among special education teachers in Pakistan

Abstract: Purpose The purpose of this paper is to examine the relationship between perceived organizational support (POS), organizational commitment and job satisfaction among special education teachers in Pakistan. The data were collected from 85 special education teachers from different special education centers in Punjab, Pakistan. POS was measured using a survey of POS developed by Eisenberger et al. (1986). Affective continuance and normative commitment are measured by affective continuance and normative commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
4
22
1
6
Order By: Relevance
“…Maintaining commitment of employees within their organization is the biggest challenge (Bibi et al , 2019). Studies have revealed that career commitment positively affects organizational commitment (Abdullah and Ramay, 2012; Nazish et al , 2013; Odunayo et al , 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Maintaining commitment of employees within their organization is the biggest challenge (Bibi et al , 2019). Studies have revealed that career commitment positively affects organizational commitment (Abdullah and Ramay, 2012; Nazish et al , 2013; Odunayo et al , 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The findings of these studies, which were conducted during the pandemic in different countries with different samples, show that OS provided during this time positively affects employees’ levels of OC. Referring to employees’ feelings of loyalty for their organizations of employment, OC [ 70 ] is closely related with OS [ 161 ], because employees’ OC can be improved with the organization’s OS behavior [ 162 ]. Moreover, this relationship can be explained within the scope of SET.…”
Section: Discussionmentioning
confidence: 99%
“…Dado que el sector educativo depende en gran medida de sus colaboradores (docentes y asistentes de la educación), las jefaturas deben prestar atención en considerar estrategias para mejorar los niveles de compromiso organizacional, de manera transversal. Para ello deben evaluarse los sistemas de compensación existentes y de reconocimiento profesional; motivar a los empleados mediante la asignación de tareas significativas y crear un ambiente de trabajo inspirador que entusiasme a los funcionarios, poniendo especial énfasis en aquellas acciones orientadas al aumento del sentido de reciprocidad de los funcionarios con la organización (Bibi, Khalid & Hussain, 2019;Cheah, Chong, Yeo & Wei Pee, 2016;Raza & Bashir, 2015).…”
Section: Discussionunclassified